Rethinking the knowledge bearing capacity of e-Business systems - Daniel F. Botha (South African Journal of Business Management, 2007)
Research was conducted in the area of sustainable knowledge extraction from e-business systems and technologies by exploring differentiating approaches from three notable authors seeking some common denominator to apply to a convergent approach in system conceptualization and design. It will be argued that most of e-business system upgrades and modification cost could be averted if the knowledge bearing capacity of proposed systems is realized and included as primary design parameters during the System Development Life Cycle. It will furthermore be argued that if this inclusive and integrative approach is followed it would lead to building a capacity to act that could be utilized for creating sustainable competitive advantage. Most e-Business system development is approached from an information processing and efficiency dimension, which more often than not exclude the knowledge utilization and effectiveness component as a design parameter. In most cases the primary focus is on information intensive functions, business process reengineering/automation and transaction processing whilst the use of information to discover knowledge assets and to innovate only comes into prominence after system implementation. This line of design thinking leads to the emergence of dominant designs which extend the scope for standardization whilst simultaneously limiting the scope for system variation. It will be proposed that re Boisot (1999), N-learning (neo-classical) thinking is normally dominant to S-learning (Schumpeterian) thinking during the e-business system design phase. The paper primarily draw on Max Boisot's Evolutionary Production Function and I-Space theoretical approach, Donald Marchand's Four Fundamental Principles of using Information to Create Business Value and Yogesh Malhotra's model on Balancing Design and Emergence for EBusiness Model Innovation. A new construct called the Knowledge Prospect Domain (KPD) will be identified and introduced as a common denominator between the models of the three authors on which to ground the approach to new thinking on e-business system design. To facilitate argumentation an attempt will be made to position the extant status of e-business systems in the I-Space, referring to what will be proposed as proprietary technologies and emergent technologies.
Keywords: 650